2009
DOI: 10.1002/cncr.24406
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide concomitant and adjuvant to radiotherapy in elderly patients with glioblastoma

Abstract: BACKGROUND: A recent randomized study conducted on newly diagnosed glioblastoma (GBM) patients demonstrated that concomitant and adjuvant temozolomide added to standard radiotherapy had a survival advantage compared with radiotherapy alone. The overall survival benefit of this aggressive treatment, however, was attenuated in older or poor performance status patients. The aim of the present study was to verify the activity and the toxicity of temozolomide administration concurrent and adjuvant to radiotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(119 citation statements)
references
References 14 publications
7
111
1
Order By: Relevance
“…43 In addition, the observation that 74% of patients with glioblastoma who survive for >5 years have MGMT promoter methylation-as opposed to <50% in an unselected population of glioblastoma patients-also underlines the prognostic value of MGMT status. 44 Nevertheless, long-term survival can be observed even in the absence of MGMT promoter methylation, indicating that MGMT promoter methylation is only one aspect of a very complex biological system.…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…43 In addition, the observation that 74% of patients with glioblastoma who survive for >5 years have MGMT promoter methylation-as opposed to <50% in an unselected population of glioblastoma patients-also underlines the prognostic value of MGMT status. 44 Nevertheless, long-term survival can be observed even in the absence of MGMT promoter methylation, indicating that MGMT promoter methylation is only one aspect of a very complex biological system.…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…Although the reported rates of acute toxicities do not seem much different between younger and older patients, the elderly may have a higher rate of delayed cognitive decline [25]. There are data suggesting that MGMT promoter methylation status in elderly patients has a similar distribution and prognostic importance to those seen in younger patients [24,25]. Although testing the MGMT promoter methylation status in younger patients (outside a clinical trial) currently does not influence the decision about which treatment the patient should receive, this might be a helpful adjunct in elderly, more frail patients in whom the risks and benefits of adding TMZ need to be weighed with particular caution.…”
Section: Should the Results In Gbm Be Extrapolated To Patients Aged >mentioning
confidence: 92%
“…Although the reported rates of acute toxicities do not seem much different between younger and older patients, the elderly may have a higher rate of delayed cognitive decline [25]. There are data suggesting that MGMT promoter methylation status in elderly patients has a similar distribution and prognostic importance to those seen in younger patients [24,25].…”
Section: Should the Results In Gbm Be Extrapolated To Patients Aged >mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal management of this CNS neoplasm in the elderly is still a matter of debate, with several combinations beings studied. A number of small, prospective studies have shown the benefit of a tri-modal approach involving chemotherapy, radiation therapy, and surgical resection in elderly patients [4][5][6][7][8]. Most recently, RTOG studied the use of upfront stereotactic radiosurgery, radiation therapy, and carmustine (BCNU) versus radiation therapy and BCNU alone.…”
Section: Introductionmentioning
confidence: 99%